Unpacking the work-life balance-performance link: Engangement and job satisfaction as mediators - Markha, Naila Hidayatul; Fuad, Eko Nur (Journal of Management and Digital Business, 2026)
This study examines the effect of work-life balance on employee performance, with employee engagement and job satisfaction tested as parallel mediators. Using a quantitative design, we surveyed 115 production employees at a garment manufacturing company in Jepara, Indonesia, selected through purposive sampling. Data were collected using a 5-point Likert-scale questionnaire and analyzed using PLS-SEM. The results show that work-life balance does not have a significant direct effect on employee performance. However, work-life balance has a positive and significant effect on both employee engagement and job satisfaction, and each mediator, in turn, has a positive and significant effect on employee performance. These findings confirm full mediation in a parallel model, with the employee engagement pathway (cognitive motivational) stronger than the job satisfaction pathway. Practically, organizations should prioritize work-life balance policies that foster engagement to improve performance. This study is limited by its cross-sectional design and focus on a single manufacturing industry, which may constrain the generalizability of the results.